Cirrhosis outcomes on rurality and weekend admissions revisited: A contemporary analysis of the national inpatient sample - Ahamed Khalyfa; Betty H. Tu; Qianyi Shi; Tomohiro Tanaka (PLoS ONE, 2026)
Background and Aims The impact of hospital rurality and weekend admission on outcomes in decompensated cirrhosis remains unclear. Studies suggest mixed effects of weekend admission on mortality and increased mortality in rural hospital admissions for decompensated cirrhosis. This study evaluated the influence of hospital rurality, weekend admission, and their interaction on outcomes in decompensated cirrhosis from 2016 to 2020. Methods A cross-sectional analysis of the National Inpatient Sample (NIS) assessed in-hospital mortality (primary outcome), likelihood of specific procedures (esophagogastroduodenoscopy, paracentesis, TIPS, hemodialysis), and time to first procedure. Regression models adjusted for demographics, liver disease etiology, clinical severity (APR-DRG mortality risk), and other factors. Results Among 11,845,223 hospitalizations, rural hospitalizations were linked to lower in-hospital mortality (OR: 0.84; 95% CI: 0.80–0.86) and higher transfer rates for severe cases (7.2% vs. 2.8%, p < 0.001). Weekend admissions showed a statistically significant but only modest reduction in mortality odds (OR: 0.99; 95% CI: 0.975–0.998). No significant interaction existed between rurality and weekend admission regarding mortality. Rural hospitals showed lower odds of performing procedures (95% CIs < 1), though time to procedure was comparable, except for earlier hemodialysis (−1.35 days; 95% CI: −2.59 to −0.11). Weekend admissions did not significantly impact procedure rates, except for paracentesis (OR: 0.94; 95% CI: 0.88–0.99). Conclusions Using a national cohort of hospitalized patients with decompensated cirrhosis, we showed that rural hospitals exhibited lower in-hospital mortality, fewer procedures, and higher transfer rates, and that weekend admissions showed only a minimal, clinically insignificant reduction in mortality, irrespective of hospital rurality.